Abnormal lipid rafts related ganglioside expression and signaling in T lymphocytes in immune thrombocytopenia patients. (2nd January 2016) - Zhang, Xian; Zhang, Donglei; Liu, Wenjie; Li, Huiyuan; Fu, Rongfeng; Liu, Xiaofan; Xue, Feng; Yang, Renchi
Abstract: Aberrant T lymphocytes signaling is considered to play a crucial role in the abnormal immune state of primary immune thrombocytopenia (ITP). Lipid raft has been verified to engage in the T cell receptor (TCR)-mediated T lymphocytes signal transduction. Whether lipid raft-associated T cells signal transduction has impact on the pathogenesis of ITP is still unconfirmed. In this study, we aimed to reveal the abnormality in structure and function of lipid rafts (LRs) in CD4 + and CD8 + T lymphocytes of patients with ITP. Our results showed that there was an increased lipid raft aggregation in ITP patients, while this kind of increase would not be influenced by platelet counts or therapeutic regimes. Stimulation by anti-CD3/CD28 monoclonal antibodies promoted enhanced lipid raft clustering in T lymphocytes of ITP patients compared with negative controls. Methyl-β-cyclodextrin (MβCD) could block the abnormal lipid raft aggregation and disrupt the TCR-mediated T cells proliferation and cytokines secretion, including both proinflammatory cytokines and anti-inflammatory cytokines. The spontaneous activation of T lymphocytes from ITP patients might be due to the elevated co-localization of protein tyrosine phosphatase (PTP) CD45 and lipid rafts in patients' CD4 + and CD8 + T lymphocytes. These findings suggest that the autoactivation of T lymphocytes from ITP patients may lead to the abnormality in lipid raft structure and raft-anchored proteins, and the changes conversely promote the TCR-mediated T cells activation of ITP patients.